Resiliensi Remaja di Karawang dengan Orang Tua Bercerai: Ditinjau dari Self-Esteem dan Religiusitas - Hanan Triatusholihah; Wina Lova Riza; Devi Marganing Tyas (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The high divorce rate in Karawang has a significant impact on the psychological condition of adolescents, particularly in relation to their ability to adapt positively, or what is known as resilience. This study aims to determine the influence of self-esteem and religiosity on resilience in adolescents with divorced parents. Using a quantitative approach with a causal associative design, this study involved 395 respondents aged 10–21 years in Karawang with divorced family backgrounds. This study used the Rosenberg Self-Esteem Scale (RSES) to measure self-esteem, the Centrality of Religiosity Scale (CRS) to measure religiosity, and the Resilience Quotient Scale (RQ) to measure resilience. Simultaneously, self-esteem and religiosity contributed 12.4% to resilience, with religiosity playing a more dominant role than self-esteem. The results of this study also showed that self-esteem had a positive and significant effect on adolescent resilience (t = 2.257; p = 0.025). Religiosity also has a positive and significant effect on adolescent resilience (t = 6.020; p = 0.000). The findings of this study confirm that higher levels of self-esteem and religiosity contribute to increased resilience in adolescents in coping with the impact of parental divorce.